Observation of Optical Precursor in Time‐Energy‐Entangled W Triphotons - Zhou Feng; Rui Zhuang; Sinong Liu; Guobin Liu; Kangkang Li; Yanpeng Zhang (Advanced Science, 2025)
Abstract In quantum communication and quantum computation, adding each entangled photon leads to an exponential increase in communication and computational capabilities. Utilizing a fifth‐order nonlinear process, narrow‐band non‐Gaussian W‐triphotons are experimentally generated through the spontaneous six ‐wave mixing (SSWM), but the manipulation of such entangled state in the group delay regime is still lacked. For the first time, the observation of optical precursors at the triphoton level is reported through the SSWM process. By appropriately adjusting the optical depth, optical precursors are effectively separated from the main wave through utilizing the slow‐light effect to manipulate the triphoton temporal correlations in the group delay regime. In biphoton and conditional two‐photon, the intensity ratio between the precursor and the main wave is tunable by adjusting the detuning and power of the laser. These pivotal breakthroughs mark a significant advancement in the study of optical precursors and open new possibilities for their application in quantum technologies.